Um porto para outros mundos: os caminhos e alternativas do Fórum Social Mundial - Müller, Bruno Frederico (2013)
The purpose of this work is to discuss the World Social Forum, its meaning and its importance in the present historic moment. Given the importance of explaining the surging of our object of study, we search back the historic processes of globalization and the expansion of transnational activism. After this first part of our work, we study our object directly, analyzing its history, internal cleavages, challenges and some emerging proposals and alternatives from within it. One of our premises is that the World Social Forum is part of the process of developing global civil society and global conscience. From this premise surges the need of approaching the concept of cosmopolitanism as praxis to this emerging global society. Underlying this work is our belief in the need of searching back the critical analysis of the State as a fundamental component of the comprehension of the political, economical and social reality, and the need of guiding the academic studies towards a simultaneously critical and transforming perspective of this reality